Taxonomic composition, abundances, and biovolumes of prey organisms in in-situ grazing experiments with Eudiaptomus gracilis in Upper Lake Constance (Überlinger See) in autumn 1998 - Kunzmann, Alessandra Janina; Ehret, Harald; Yohannes, Elizabeth; Straile, Dietmar; Rothhaupt, Karl-Otto (Supplement to: Kunzmann, AJ et al. (2019): Calanoid copepod grazing affects plankton size structure and composition in a deep, large lake. Journal of Plankton Research, 41(6), 955-966, https://doi.org/10.1093/plankt/fbz067, 2019)
The dataset compiles cell counts and biovolumes of different plankton groups (phytoplankton, ciliates, rotifers, heterotrophic nanoflagellates, and bacteria) obtained from three in situ bottle experiments conducted in September/October 1998 with the copepod Eudiaptomus gracilis as grazer.
Keywords: bottle experiment; ciliates; grazing; Phytoplankton; rotifers